Thermal Load Induced Changes of Hygric and Thermal Properties of Glass Fiber Reinforced Cement Composites - Cerny, Robert; Totova, Michaela; Toman, Jan; Drchalova, Jaroslava; Rovnanikova, Pavla; Bayer, Patrik (Communications - Scientific letters of the University of Zilina, 2002)
The effect of thermal load on the basic thermal and hygric properties of two types of glass fiber reinforced cement composites (GFRCC) is analyzed in the paper. Thermal conductivity, specific heat and moisture diffusivity are determined after high temperature exposure to 600 and 800 °C. A decrease of thermal conductivity as high as 50 % and an increase of moisture diffusivity in the range of one to two orders of magnitude are observed for all types of the studied materials after heating to 800 °C. On the other hand, specific heat and density in the same situation decrease by only about 10 %. In the analysis of the reasons for the measured differences between hygric and thermal parameters of thermally loaded and unloaded samples, pore distribution measurements, scanning electron microscopy and thermal analysis are employed.